Dichoptic Vision Therapy in Adults with Anisometropic Amblyopia: A Systematic Review - Ghoshal, Rituparna; Ghosh, Dipanwita; Ghosh, Somnath (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Amblyopia is a condition with reduced best corrected visual acuity in absence of any ocular pathology. Different treatment approaches of amblyopia have been researched for decades. Recent studies on binocular dichoptic therapy using different software and video game based training showed drastic improvement in visual functions in amblyopic adults. Aim of this review is to assess the effect of vision therapy with dichoptic training in adults with anisometropic amblyopes. Method: Review was conducted in articles published within last 25 years from databases like PubMed, research gate, google scholar. Results: Dichoptic therapy has promising results in treatment of adults with anisometropic amblyopia. However, several limitations of these said researches were observed. Conclusion: Further studies particularly RCTs with strict methodology and treatment protocol, larger sample size and longer follow ups are recommended before clinicians could impart dichoptic therapy as a management option of adults with amblyopia into their evidence based practice.